SALT TOLERANCE OF TURF GRASS Puccinellia distans: I. GROWTH RESPONSE AND ION ACCUMULATION - Didy Sopandie; Masumi Moritsugu; Toshio Kawasaki (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 1995)
The aim of this study was to see the salt tolerance of turf grass Puccinellia distans in term of ion accumulation and ionic interactions under salt stress condition. Plants were grown hidroponically in culture solution with addition of NaCI (0, 25, 50, 100 and 200 mM). High concentrations of NaCI brought about growth reduction; the decrease of shoot dry matters was in the range of 30-84% and 30- 70% for root dry matters. Although the yield of plants decreased so much in the presence of 200 mM NaCI, but plants were able to remain alive without showing any visible symptoms of injury. Much more Na was accumulated in the roots than in the shoots. Exposing plants to salinity result in the decrease of K, Ca, and Mg contents.